Institutional isomorphism and the persistence of the present international order - Ramon Fernandes, Vítor (2019)
International orders reflect the settled arrangements that define relations between states in certain moments in history. Order breaks down when the adopted set of organizational principles that define roles and the terms of those relations cease to operate. International organizations are a central feature of the current order and an important source of legitimacy. This article extracts a set of ideas derived from the new sociological institutionalism literature in organizational analysis and sets out an argument showing their possible implications for the present order. I argue that there are certain organizational features related to institutional isomorphism that may well support the persistence and maintenance of the current international order. The argument is based on the homogeneity of practices and arrangements found in different institutions and organizations. The persistence of those practices and their reproduction in structures are to some extent self-sustaining and may provide additional support to the idea that the current American-led international order may last longer than is often thought while allowing for changes in the distribution of power.